EU consumers' quantitative inflation perceptions and expectations: An evaluation - Rodolfo Arioli; Colm Bates; Heinz Dieden; Ioana Duca; Roberta Friz; Christian Gayer; Geoff Kenny; Aidan Meyler; Iskra Pavlova (European Central Bank (ECB), 2017)
This report updates and extends earlier assessments of quantitative inflation perceptions and expectations of consumers in the euro area and the EU using an anonymised micro data set collected by the European Commission in the context of the Harmonised EU Programme of Business and Consumer Surveys. Confirming earlier findings, consumers' quantitative estimates of inflation are found to be higher than actual HICP (Harmonised Index of Consumer Prices) inflation over the entire sample period (2004-2015). The analysis shows that European consumers hold different opinions of inflation depending on their income, age, education and gender. Although many of the features highlighted for the EU and the euro area aggregates are valid across individual Member States, differences exist also at the country level. Despite the higher inflation estimates, there is a high level of co-movement between measured and estimated (perceived/expected) inflation. Even respondents providing estimates largely above actual HICP inflation, demonstrate understanding of the relative level of inflation during both high and low inflation periods. Based on these economically plausible results, the report concludes that further work should be devoted to defining concrete aggregate indicators of consumers' quantitative inflation perceptions and expectations on the basis of the dataset used in this study. Moreover, it outlines a number of future research topics that can be addressed by exploiting the enormous potential of the data set.
Keywords: D8; D12; E31; 330; Harmonised EU Programme of Business and Consumer Surveys; inflation perceptions; inflation expectations; quantitative and qualitative indicators; micro data set; consumers; co-movement; HICP